Survival - Bradford, Chris (Bradford, Chris. Bodyguard, 2017)
After their convoy is ambushed by rebel soldiers, teenage bodyguard Connor along with Amber and Henri, whom he is sworn to protect, must fight for their lives in the African plains, evading lethal hunters, both human and animal.